Application of dengue diagnostic tests as point-of-care testing by Myanmar General Practitioners: did young GPs use more than senior GPs? - Tin, Myo Han; Tin Tin , Hla; Swe, Swe Latt; Than , Soe T; Win , Zaw; Tin , Aye; Khine, SW; Thuraiappah, DM (Academy of Family Physicians of Malaysia and Family Medicine Specialist Association, 2015)
Background: Early detection of dengue cases via general practitioners (GPs), major primary care providers is an effective strategy in mitigation of dengue burden in Myanmar. Confirmation of dengue cases using laboratory tests is recommended by W.H.O for clinical management, prevention and control activities. Nevertheless, evidence on dengue diagnostic tests used by Myanmar GPs as point-of-care testing (POCT) has not been founded yet. Objective: To compare dengue diagnostic tests used as POCT between young GPs and senior GPs Methods: A cross-sectional descriptive and analytical study was conducted in August, 2015 among 72 GPs in Yangon. A pre-tested questionnaire was used to collect data regarding demo-academic and practice-background, dengue diagnostic tests used for POCT and its reasons. GPs aged under 30 years and currently practiced for 1-5 years as young GPs and their counter-part were defined as senior GPs for inferential analysis. Results: Young GPs and senior GPs were 35% (25/72) and 24% (17 /72) respectively while others 41% (30/72) were in-active in practice and did not meet with young-senior GPs definition. Dengue diagnostic tests application was still limited in GPs’ clinics. NS1-RDT (20.8%) was mostly used followed by Hess’s test (19.4%), NS1+IgM/IgG-RDT(18.1%),IgM/IgG-RDT(16.7%),WHO-clinical-criteria+NS1+ IgM/IgM-RTD+ Out-break information (16.7%) and WHO-clinical-criteria+NS1+ IgM/IgG-RDT(11.2%). Although both young and senior GPs did not use ELISA tests as POCT, 2.8 % of other GPs used it. Senior GPs used Hess’s tests significantly more than young GPs (35% vs 20%). WHO-Clinical-criteria+ outbreak information with RDT tests were more used by young GPs, but it was not statistically significant. Following clinical guideline, confirmation of cases, easy to perform, cost and market availability were reasons given for using the tests. Conclusion: Low utilization of dengue diagnostic tests highlighted to promote adherence of W.H.O recommendation among Myanmar GPs. POCT training should be arranged. A further study is needed for more valid findings.